(untitled) (Revista Sistemas de Producción Agroecológicos, 2024)
Cattle in extensive grazing in the low tropics survive different nutritional, health and well-being limitations, which constantly challenge human capacity to provide them with improvement plans capable of generating adaptability to the productive context, reducing the adversities of an environmental and social environment. The objective of this research was to analyze the interaction times and preference of environmental enrichment elements, the human-animal relationship and weight gain of grazing cattle in the low tropics. For this, 26 cattle were used, which graze in natural extensive systems, randomly divided into two groups, the first called G1C control, in which elements of environmental enrichment were non-existent in the grazing areas. On the other hand, group two called G2EA, which was integrated for one hour (9:00 am to 10:00 am) in a modified environment enriched with tires, commercial brushes and handmade brushes. The animals were evaluated for 20 hours for 4 weeks. In these observations, the times of physical contact and interaction with the enriched elements, the human-animal relationship were assessed through 5 Welfare Quality tests of approach-avoidance fear and weight gain during the test. The data were analyzed with the statistical program SAS® Software, version 9.4. It was identified that environmental enrichment had significant behavioral effects on some of the variables analyzed such as the human-animal relationship, with the G2EA group being the one that presented the highest percentages of animals that allowed positive consolidation. The interaction with the enrichment elements that captured the highest percentage of use was the static commercial brush. Environmental enrichment gives the cattle in this experiment beneficial effects of the human-animal relationship, positive effects for weight gain. It is necessary to carry out more studies, with a greater number of animals of different age groups and production techniques, testing different modified environments.